Peachtree Borer, Synanthedon exitiosa (Say) (Insecta: Lepidoptera: Aegeriidae) - J. Stacy Strickland (EDIS, 2005)
The peachtree borer, Synanthedon exitiosa (Say), is a very serious agronomic pest. The peachtree borer and the lesser peachtree borer, Synanthedon pictipes, account for more damage to peach trees than all other insect pest combined. The peachtree borer can damage the tree in two ways: girdling and inducing plant pathogens to invade the weakened tree. This document is EENY-260 (IN524), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002. Reviewed: December 2005.